2016
DOI: 10.1515/cjf-2016-0023
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Role of Vitamin C and Chitosan Against Paraquat-induced Oxidative Stress in Muscles of Common Carp (Cyprinus carpio)

Abstract: The purpose of this study was to examine the effects of antioxidants, including vitamin C, chitosan or a combination of both, on oxidative stress markers in muscles, as edible tissues of fish, exposed to paraquat. Fish exposed to 0.02 mg/L paraquat for 21 days were fed different diets: a normal diet, a diet containing chitosan (1000 mg/kg diet), a diet with vitamin C (1000 mg/kg diet) or both vitamin C and chitosan. Oxidative stress markers, including the activity of catalase, total antioxidant and malondialde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…The level of LDH was elevated in the DOX-administered animals compared to animals in the other experimental groups, which confirms tissue injury [43]. Sharifinasab et al reported that the administration of CNPs can regulate the level of LDH [44]. Similarly, reduced levels of LDH were produced in the serum compared to DOXadministered rats upon the administration of CNPs and DCNPs (Figure 5).…”
Section: Analysis Of Cardiac Biomarkerssupporting
confidence: 65%
“…The level of LDH was elevated in the DOX-administered animals compared to animals in the other experimental groups, which confirms tissue injury [43]. Sharifinasab et al reported that the administration of CNPs can regulate the level of LDH [44]. Similarly, reduced levels of LDH were produced in the serum compared to DOXadministered rats upon the administration of CNPs and DCNPs (Figure 5).…”
Section: Analysis Of Cardiac Biomarkerssupporting
confidence: 65%
“…This improvement in activities of the antioxidant enzymes GPx and SOD caused by C. pepo fruit extract could be likely due to its ascorbic acid [35], α-tocopherol [36] and selenium [37] composition. In the work of Sharifinasab and coauthors, combined supplementation with ascorbic acid and chitosan enhanced the detoxification system in fish muscles and protect against paraquat toxicity [38]. Vitamin C is effective in scavenging free radicals; such as hydroxyl radicals, aqueous peroxyl radicals and superoxide radicals and confers protection to the cell by donating electron to reduce these radicals, thus neutralizing their effects [23].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, dietary intake of chitin or chitosan was found to improve hypoxia tolerance in Litopenaeus vannamei and Penaeus monodon (Niu et al 2011;Niu et al 2013), thermal (34°C) stress tolerance in Rutilus frisii kutum (Najafabad et al 2016) and ammonia tolerance in Litopenaeus vannamei (Chen et al 2020d). Further, dietary supplementation of chitosan/chitosan nanoparticle along with vitamin C reduced pesticide toxicity in common carp and tilapia (Sharifinasab et al 2016;Naiel et al 2020). Also, inclusion of Chi92 (a chitinase with high b-glucanase activity) to zebrafish diets containing yeast products was shown to improve disease resistance (Huo et al 2016).…”
Section: Biological Derivativesmentioning
confidence: 93%
“…Further, dietary supplementation of chitosan/chitosan nanoparticle along with vitamin C reduced pesticide toxicity in common carp and tilapia (Sharifinasab et al . 2016; Naiel et al . 2020).…”
Section: Stress Mitigation Through Dietary Additives/nutraceuticalsmentioning
confidence: 99%